Innovation in Public Service Management in an Effort to Increase Economic Investment in Indonesia - Rizal S, Muh; Kurniawan, Kurniawan; Abdullah, Faizal; Hikmah, Nurul Hidayatun (Pinisi Business Administration Review, 2025)
This research discusses public service management innovation in an effort to increase investment in Indonesia. This article is based on Law Number 25 of 2009 concerning Public Services. This research method uses a qualitative descriptive approach. Data collection techniques were carried out through library studies and online data documentation. The focus of this article is the concept of public service management innovation in an effort to increase economic investment as well as forms of implementing public service innovation in an effort to increase economic investment in Indonesia. The results of the discussion show that (1) Public service management innovation has several service dimensions, namely, reliability, responsiveness, assurance, empathy, and physical evidence. The government's steps as the public sector in encouraging investment include providing assistance to business actors, developing infrastructure, improving regulations and improving the licensing process. (2) Forms of implementing public service management innovations in an effort to increase economic investment in Indonesia include Electronic Integrated Licensing System (OSS), E-Government, Integrated Investment Monitoring System, One Stop Integrated Services (PTSP), Integration between Central and Regional Governments, Elimination of Overlapping Regulations, More Flexible Regulations, Training and Development of Public Employees, Adequate Supporting Infrastructure, Whistleblowing System, Public Service Quality Assessment System, Private Involvement in Service Provision, Special Economic Zones (SEZ), and the existence of an Investment Information Portal.Keywords: Innovation, Public Services, Investment, Economy